Evolutionary Origins of the Fumonisin Secondary Metabolite Gene Cluster in Fusarium verticillioides and Aspergillus niger - WOLFE, KENNETH (SAGE-Hindawi, 2011)
The secondary metabolite gene clusters of euascomycete fungi are among the largest known clusters of functionally related genes in eukaryotes. Most of these clusters are species specific or genus specific, and little is known about how they are formed during evolution. We used a comparative genomics approach to study the evolutionary origins of a secondary metabolite cluster that synthesizes a polyketide derivative, namely, the fumonisin (FUM) cluster of Fusarium verticillioides, and that of Aspergillus niger another fumonisin (fumonisin B) producing species.We identified homologs in other euascomycetes of the Fusarium verticillioides FUM genes and their flanking genes.We discuss fourmodels for the origin of the FUM cluster in Fusarium verticillioides and argue that two of these are plausible: (i) assembly by relocation of initially scattered genes in a recent Fusarium verticillioides; or (ii) horizontal transfer of the FUM cluster from a distantly related Sordariomycete species. We also propose that the FUM cluster was horizontally transferred into Aspergillus niger, most probably from a Sordariomycete species.
PUBLISHED
Keywords: Immunology; Genetics; Fusarium verticillioides; Aspergillus niger